Computational methods for estimating energy expenditure in human physical activities - Liu, Shaopeng; Gao, Robert X; Freedson, Patty S (Medicine and science in sports and exercise, 2012)
Accurate and reliable methods for assessing human physical activity (PA) energy expenditure (PAEE) are informative and essential for understanding individual behaviors and quantifying the effect of PA on disease, for PA surveillance, and for examining determinants of PA in different populations. This article reviews recent advances in the estimation of PAEE in three interrelated areas: 1) types of sensors worn by human subjects, 2) features extracted from the measured sensor signals, and 3) modeling techniques to estimate the PAEE using these features. The review illustrates three directions in the PAEE studies and provides recommendations for future research, with the aim to produce valid, reliable, and accurate assessment of PAEE from wearable sensors.